Pendidikan Anak dalam Perspektif Al-Qur’an - Khairun Nisa' (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2021)
Abstract The way parents take care of their children is by educating and teaching good morals and protecting them from a bad environment. When parents see signs that their children have been able to distinguish between good and bad, they should increase their supervision.Children are a trust for both parents. Al-Qur'an as a source of Islamic teachings also reveals the concept of ideal education. in this paper will be put forward about children's education in the perspective of the Qur'an by using a literature review. This paper produces a collection of theories about children's education, verses relating to the meaning of children's education. Keywords: Pendidikan, Al-Quran